Atherogenic Role of LDL(-) on Macrophages - Núria Puig; Berta Casaldàliga; Pol Camps-Renom; Francesc Jiménez-Altayó; Elena Jiménez-Xarrié; Jose Luis Sánchez-Quesada; Sonia Benitez (Advanced Research in Biological Science Vol. 6, 2023)
This chapter assesses the induction of an inflammatory profile and the accumulation of intracellular lipids in macrophages by electronegative LDL (LDL(-)). LDL(-), a modified LDL that is present in blood, exerts atherogenic effects on endothelial cells and monocytes. Numerous studies focusing on LDL(-) have since been performed, and the most widely accepted idea is that LDL(-) is a pool of LDL particles modified by several mechanisms. In the study shown in this chapter, LDL(-) and in vitro-modified LDLs (oxidized, aggregated, acetylated) were added to macrophages derived from THP1 monocytes over-expressing CD14 (THP1-CD14). Then, cytokine release, cell differentiation, lipid accumulation, and gene expression were measured by ELISA, flow cytometry, thin-layer chromatography, and real-time PCR, respectively. Compared to other modified LDLs, LDL(-) caused THP1-CD14 macrophages to produce more cytokines. Additionally, LDL(-) stimulated morphological alterations linked to mature macrophages. HDL and anti-TLR4 were added to offset these effects. Macrophages ingested large amounts of LDL(-), which was the main initiator of intracellular lipid buildup in lipid droplets enriched in triglycerides. In contrast to inflammation, the addition of anti-TLR4 had no effect on lipid accumulation, thus suggesting an uptake pathway alternative to TLR4. In our study, compared to other in vitro-modified LDLs, LDL(-) was the main inductor of GM-CSF, IL6, and IL10 release, and it had a similar effect on IL1\(β\) than oxLDL. This occurred in the absence of changes in cell proliferation or mortality. In this regard, LDL(-) upregulated the expression of the scavenger receptors CD36 and LOX-1, as well as several genes involved in TG accumulation. In summary, LDL(-) promoted macrophage differentiation, inflammation, and triglyceride-enriched lipid droplets formation in THP1-CD14 macrophages, probably through different receptors. The complex interaction between these pathways should be addressed in future studies. Taken together, our findings highlight new significant actions of LDL(-) on macrophage activation in the context of the development of atherosclerosis.